2008
DOI: 10.1016/j.adolescence.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate self‐harm in adolescents: Comparison between those who receive help following self‐harm and those who do not

Abstract: This international comparative study addresses differences between adolescents who engage in deliberate self‐harm (DSH) and who receive help following the DSH episode versus those who do not. A standardised self‐report questionnaire was completed by pupils aged 14–17 in Australia, Belgium, England, Hungary, Ireland, The Netherlands, and Norway (n = 30 532). An act of DSH in the year prior to the study was reported by 1660 participants. Nearly half (48.4%) had not received any help following DSH, 32.8% had rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
120
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(127 citation statements)
references
References 15 publications
5
120
1
1
Order By: Relevance
“…Studies involving a longitudinal research design are required to further investigate the nature of contagious influences and to examine how episodes might cluster in time in individual institutions such as schools. The often secretive nature of DSH and the fact that only a relatively small minority of DSH episodes in adolescents in the community (especially those involving self-cutting) come to clinical attention [25,30,45] mean that preventative efforts should primarily be based on population-based initiatives directed towards all adolescents. School-based initiatives seem most appropriate [12] and [23, pp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving a longitudinal research design are required to further investigate the nature of contagious influences and to examine how episodes might cluster in time in individual institutions such as schools. The often secretive nature of DSH and the fact that only a relatively small minority of DSH episodes in adolescents in the community (especially those involving self-cutting) come to clinical attention [25,30,45] mean that preventative efforts should primarily be based on population-based initiatives directed towards all adolescents. School-based initiatives seem most appropriate [12] and [23, pp.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has shown that the levels of self-poisoning and self-injury in adolescents in the community are far greater than is apparent from hospital-based studies [9]. Furthermore, selfcutting is more common than self-poisoning amongst adolescents in the community [23,30], with self-poisoning being the main factor likely to lead to presentation to clinical services following DSH [24,45]. Also, self-cutting is likely to be repeated, often on many occasions [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, a more recent schoolbased study of adolescent self-harm using the same CASE methodology found that 18% of female and 6.4% of male post-primary school students reported a lifetime history of selfharm (Doyle, Treacy & Sheridan, 2015). A common finding in all of the CASE studies was that only a small minority of those who self-harmed actually presented to hospital or sought professional help meaning that most adolescent self-harm was 'hidden' from the health services (Ystgaard et al, 2009;. Teachers and school counsellors are therefore often the only professionals that self-harming adolescents have regular contact with and are in a prime position to respond to students' distress.…”
Section: Introductionmentioning
confidence: 98%
“…Whereas much research has highlighted the characteristics of those individuals who present to hospital following self-harm, there are relatively few largescale studies of adolescent self-harm in the community (O'Connor et al, 2009). This is problematic as the majority of adolescents who self-harm do not present to clinical services (Groholt, Ekeberg, Wichstrom, & Haldorsen, 2000;Ystgaard et al, 2009;King, 1997).…”
mentioning
confidence: 99%